Analisis kebutuhan pembelajaran fisika di SMAN 1 Padang (dalam rangka pembuatan aplikasi penilaian keterampilan proyek) - Asmi Putri; Renol Afrizon; Festiyed Festiyed; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2020)
In the 4.0 industrial revolution the world experienced rapid changes due to the rapid development of information technology. The development of technology has an impact on the world of education. Various attempts have been made by the government to deal with technological and information developments including curriculum and program changes that can improve teacher competency. In learning can not be separated from the assessment process. Assessments are given for each student activity for example assessments on project task. Teachers must be innovative, creative and able to develop and use learning media that are in line with the development of science and technology. Researchers are interested in making assessment applications that can be used as a medium to assist teachers in the assessment process of assignments given to students. The type of research in accordance with the problems and objectives that have been raised is analysis. The researcher conducts a needs analysis in the context of the need to make an appraisal application. This analysis was conducted at SMAN 1 Padang in class XI which was conducted by distributing questionnaires to students and teachers. Questionnaires given to respondents have been validated by experts and can be used. The instrument used in this study was a questionnaire sheet containing positive and negative responses. The data analysis technique used in this study uses descriptive statistical analysis. Based on the results of the needs analysis that is not optimal implementation of learning in the realm of skills, assessments conducted by teachers are more focused on the realm of knowledge with assignments in the form of physics questions, project assignments are still not optimal, the use of technology that is not optimal in conducting assessments, and media / the material given has not been interesting. Therefore, researchers designed a project skills assessment application called Project Valuer.In the 4.0 industrial revolution the world experienced rapid changes due to the rapid development of information technology. The development of technology has an impact on the world of education. Various attempts have been made by the government to deal with technological and information developments including curriculum and program changes that can improve teacher competency. In learning can not be separated from the assessment process. Assessments are given for each student activity for example assessments on project task. Teachers must be innovative, creative and able to develop and use learning media that are in line with the development of science and technology. Researchers are interested in making assessment applications that can be used as a medium to assist teachers in the assessment process of assignments given to students. The type of research in accordance with the problems and objectives that have been raised is analysis. The researcher conducts a needs analysis in the context of the need to make an appraisal application. This analysis was conducted at SMAN 1 Padang in class XI which was conducted by distributing questionnaires to students and teachers. Questionnaires given to respondents have been validated by experts and can be used. The instrument used in this study was a questionnaire sheet containing positive and negative responses. The data analysis technique used in this study uses descriptive statistical analysis. Based on the results of the needs analysis that is not optimal implementation of learning in the realm of skills, assessments conducted by teachers are more focused on the realm of knowledge with assignments in the form of physics questions, project assignments are still not optimal, the use of technology that is not optimal in conducting assessments, and media / the material given has not been interesting. Therefore, researchers designed a project skills assessment application called Project Valuer.